1967
DOI: 10.1182/blood.v30.4.513.513
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: The Exacerbation of Hemolysis in Paroxysmal Nocturnal Hemoglobinuria by Strenuous Exercise

Abstract: Muscular exercise in patients with paroxysmal nocturnal hemoglobinuria has been shown to result in systemic acidosis with lacticacidemia and exacerbation of in vivo hemolysis. It is suggested on the basis of this study that patients with PNH be advised to avoid severe muscular exercise. The acid hemolysis test should be performed in all patients that are suspected of having March hemoglobinuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1977
1977
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…He thought that accumulation of lactic acid from the previous day's exertion contributed to the acid environment needed to induce haemolysis. Blum et al (1967) provided experimental support for Strübing's hypothesis 85 years later when they reported that the exacerbation of haemolysis noted after strenuous exercise is associated with an increase in plasma lactic acid concentration and a concordant reduction in the pH of the blood.…”
Section: Part I the Early Historymentioning
confidence: 89%
“…He thought that accumulation of lactic acid from the previous day's exertion contributed to the acid environment needed to induce haemolysis. Blum et al (1967) provided experimental support for Strübing's hypothesis 85 years later when they reported that the exacerbation of haemolysis noted after strenuous exercise is associated with an increase in plasma lactic acid concentration and a concordant reduction in the pH of the blood.…”
Section: Part I the Early Historymentioning
confidence: 89%
“…Συχνά εμφανίζεται κατά τη διάρκεια της αφύπνισης μετά από ύπνο, κατά τη διάρκεια της ημέρας ή της νύχτας. Όπως προαναφέρθηκε, υπεύθυνη έχει θεωρηθεί η μικρή μείωση του pH λόγω της μειωμένης αναπνευστικής συχνότητας κατά τη διάρκεια του ύπνου ή μετά από οποιαδήποτε βαθμού κόπωση[Blum et al 1967], καθώς και οι διακυμάνσεις της στάθμης της κορτιζόλης κατά τη διάρκεια της ημέρας και της νύχτας, αν και η χορήγηση πρεδνιζολόνης δεν φαίνεται να επηρεάζει το νυκτερινό ρυθμό της παροξυντικής αιμοσφαιρινουρίας[Hansen 1968]. Μάλιστα, η αιμοσφαιρινουρία μπορεί να μην είναι εμφανής και να μην αναφέρεται από τον ασθενή, όταν η αιμόλυση δεν είναι σημαντική.…”
unclassified